Sustainable resource utilisation in the production of building materials - Esin, Tülay; Yüksek, Ízzet (Taylor and Francis Ltd. info@tandf.co.uk, 2013)
The impact of building materials on the environment throughout their life cycle essentially defines the total environmental impact of the buildings in which they are used [1]. Buildings have an enormous and continuously increasing impact on the environment, using about 40% of natural resources extracted in industrialised countries. In order to mitigate the impact of buildings along their life cycle, green building has emerged encouraging the use of more environmental friendly materials. The building materials with low environmental impact give significant ecological characteristics to traditional buildings. Reduced environmental impact of the production process of these materials makes them more environmentally friendly materials, because the environmental impact caused during the production process of the building materials constitutes a large portion of the total environmental impact of a building along its life cycle. This study is aimed at investigating the parameters related to the sustainable resource utilisation that provides ecological quality to building materials. This study has analysed some of the building materials produced in Turkey in terms of the environmental impacts of their production process by developing a point based method. Raw materials used for the production of building materials should not be sourced from exhaustible resources as this diminishes their natural supplies preventing their use by future generations. © 2013 Copyright Taylor and Francis Group, LLC. © 2014 Elsevier B.V., All rights reserved.
Keywords: building material; environmental effect; sustainable resource